Combined inhibition of dopamine D1/D2 receptors induces cognitive and emotional dysfunction through oxidative stress and dopaminergic neuron damage - Li, Xue; Zhuang, Yao; Zhang, Ya Ru; Fan, Ke Ke; Chen, Xin Xin; Chen, Xin Xing; Liu, Xuan Yi; Sun, Jing; Liu, Li (Frontiers in Behavioral Neuroscience, 2025)
IntroductionDopamine system dysfunction is closely associated with nervous system diseases such as Parkinson’s disease and psychiatric disorder. Current research is limited to the individual application of dopamine D1 and D2 receptor-related agents, and the systematic effects of combined dopamine D1/D2 receptor inhibition on neural function remain unclear. In this study, we aimed to investigate the dose-dependent effects of co-DR1/2I (combined administration of dopamine receptor 1 inhibitor SCH39166 and dopamine receptor 2 inhibitor raclopride) on oxidative stress, learning, memory, emotion, and motor function in the substantia nigra, striatum, and hippocampus of mice.MethodsAfter administering varying doses of co-DR1/2I through gastric tubes to male C57BL/6 mice, we used enzyme-linked immunosorbent assay to measure monoamine oxidase B (MAO-B), reactive oxygen species (ROS), and superoxide dismutase (SOD) activity. Behavioral changes were assessed, using open field, rotarod, and water maze tests. Tyrosine hydroxylase positive neurons were labeled with immunofluorescence, and tyrosine hydroxylase levels were detected by Western blot (WB) assay.ResultsLow-dose co-DR1/2I significantly increased MAO-B and ROS levels (p < 0.01) and decreased SOD activity (p < 0.01) in the substantia nigra, striatum, and hippocampus. MAO-B activity positively correlated with ROS (r = 0.916, p < 0.001) and negatively correlated with SOD (r = −0.685, p < 0.001), whereas ROS negatively correlated with SOD (r = −0.661, p < 0.001) in co-DR1/2I-treated mice. The medium- and high-dose groups exhibited spatial memory impairment (longer escape latency, p < 0.05) in the water maze and more anxiety-like behavior (reduced central zone time, p < 0.01) in the open field test; however, no abnormalities in motor coordination were observed in the rotarod test (p > 0.05). Immunofluorescence and WB confirmed a reduction in the dopaminergic neuron count after co-DR1/2I.ConclusionThis is the first study to demonstrate that co-DR1/2I triggers cognitive and emotional dysfunction by exacerbating oxidative stress and dopaminergic neuronal damage, thereby advancing our understanding of the neurotoxic mechanisms of dopamine receptor antagonists. Future studies are needed to explore targeted antioxidant therapies and receptor-selective modulation strategies to reduce the side effects.